2020
DOI: 10.3390/educsci10030060
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Feedback in Higher Education: A Review of Literature

Abstract: In raising the standards for professional educators, higher educators must be prepared to provide the highest quality feedback on student performance and work products toward improved outcomes. This review of the literature examined the major findings of 70 quantitative, mixed methods, or qualitative studies found in higher education journals across a range of disciplines. Multiple recommendations and results for feedback emerged which fall into the categories described by Susan Brookhart. This review found re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 103 publications
1
37
0
1
Order By: Relevance
“…In concurrence with Haughney 22 this paper reaffirms the need to train teachers in the provision of helpful feedback. The present paper clearly showed that interventional workshops have the potential to enhance the quality of teachers' WFB.…”
Section: O N C L U S I O Nsupporting
confidence: 60%
See 2 more Smart Citations
“…In concurrence with Haughney 22 this paper reaffirms the need to train teachers in the provision of helpful feedback. The present paper clearly showed that interventional workshops have the potential to enhance the quality of teachers' WFB.…”
Section: O N C L U S I O Nsupporting
confidence: 60%
“…1,19,20 Thus, earlier studies have considered teachers' training as instrumental to provide effective feedback. 3,5,[21][22][23] Training can enable the teachers to determine the most effective method of providing feedback in their own teaching context. 1 Nonetheless, hardly a handful of studies, have attempted to examine the effects of teacher training in any aspect of WFB to date.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Treating universities as business organisations is associated with neoliberalism, and the new public management (NPM) and performance appraisals tend to be perceived as black boxes in a larger NPM 'machine' [9]. The growing importance of the market and competition in the higher education sector brings with it an increase in the accountability of the university and its employees [10,11]. However, the traditional culture of the university is based on a large extent on Merton's CUDOS(communism, universalism, disinterestedness, organized skepticism) ethos reflected in individual commitment, scientific teamwork, dedication and intrinsic motivation over extrinsic rewards of the academic staff [12,13], which are components of public service motivation (PSM).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of higher education, parameters that touch upon students' characteristics (particularly, student engagement and motivation) coupled with learning design parameters (e.g., proper instructional feedback that accounts for the actual student needs) have received increased attention during the last decades from the educational community. This is mainly due to the fact that research suggests they are linked to high quality learning and deep student understanding [1], [2]. Furthermore, aligning the learning objectives, with the teaching methods and the student assessment is widely acknowledged in higher education [3].…”
Section: Introductionmentioning
confidence: 99%